Cellular expression of lymphocyte function associated antigens and the intercellular adhesion molecule-1 in normal tissue. - Smith, M E (1990)
A detailed immunohistological analysis of normal tissues for the distribution of lymphocyte function-associated antigens (LFA) and the intercellular adhesion molecule-1 (ICAM-1) showed several hitherto unrecognised patterns of LFA-3 and ICAM-1 expression. The widespread, but not ubiquitous, distribution of LFA-3 contrasted with the more restricted distribution of ICAM-1. Among epithelial cells, all tissues which were ICAM-1 positive were also LFA-3 positive with the single exception that thymic cortical epithelium, in contrast to previous reports, expressed only ICAM-1. It was striking that LFA-3 molecules were absent in some tissues which are considered to be sites of immunological privilege (such as brain and testis), suggesting an additional mechanism by which these microenvironments maintain immunological autonomy. Furthermore, the unexpected finding that LFA-3 is strongly expressed on intercalated discs of cardiac muscle may possibly be related to a non-immune function, or indicate a structurally similar epitope expressed by an unrelated molecule within this tissue.